The possible microbial aethiology of pyoderma among primary school children in the Ashanti region of Ghana - Akoto, Phyllis Victoria (2012)
A thesis submitted to the Board of Postgraduate Studies, Kwame Nkrumah University of Science and Technology, Kumasi, in partial fulfilment of the requirement for the award of the Degree of Master of Philosophy in Clinical Microbiology,